Paradoxical Akathisia Caused by Clonazepam, Clorazepate and Lorazepam in Patients with Traumatic Encephalopathy and Seizure Disorders: A Subtype of Benzodiazepine-Induced Disinhibition? - A. B. Joseph; B. A. Wroblewski (Behavioural Neurology)
Akathisia is frequently reported to be caused by neuroleptic drugs and sometimes by certain other agents such as fluoxetine. Benzodiazepines are a common treatment. The principal mechanism of akathisia is thought to be neurochemical, probably dopaminergic with serotonin also playing an important role. It is not usually thought to be related to benzodiazepine-caused disinhibition. Four episodes of atypical or paradoxical benzodiazepine-induced akathisia in three patients are reported and analyzed. All four episodes of akathisia were atypical because they were caused by clonazepam, clorazepate, or lorazepam. In one patient neither thiothixene nor lorazepam caused akathisia, but clonazepam and clorazepate did. In another patient both lorazepam and fluoxetine caused akathisia. It is also noted that all three patients had a history of traumatic brain injury and seizure disorder. The data support the hypothesis that atypical benzodiazepine-induced akathisia exists. Its mechanism may be different from neuroleptic-induced akathisia, but may still involve serotonergic systems or the forced normalization phenomenon. The similarity of these cases to reports of benzodiazepine-induced disinhibition raises the possibility that in some patients they may be the same entity.